Pemberdayaan Nasabah BWM Al Muna Berkah Mandiri, Bantul, Yogyakarta Dengan Pembuatan Bath Bomb Salt - Putri, Mega Karina; Dellima, Beta Ria Erika Marita; Sari, Eni Kartika (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Bath bombs are an example of a bath salt product. Using bath bombs can help moisturize the skin and brighten it, as a relaxant, so it can help reduce stress, tension and fatigue suffered by the body. By making easily from these ingredients, a cosmetic product that is useful and has high economic value can be obtained. This service program is expected to provide knowledge and skills to housewives and young women who are among the customers of BWM Al Muna Berkah Mandiri about making bath bombs with affordable capital and can develop their business products. Material presentation activities by resource persons from the service team, namely: apt. Mega Karina Putri, M. Pharm. Sci., and continued with a training session on making bath bomb salt and questions and answers. Apart from that, a pre-test and post-test were also carried out to measure participants' understanding before and after the event. Based on the results of the pretest and posttest, it was concluded that there was an increase in participants' knowledge. Participants in the very good category experienced an increase of 12% and good there was an increase of 16%, while participants in the fair category experienced a decrease of 12% and poor there was a decrease of 16%. The training participants and participant representatives expressed their gratitude because this activity was very useful in providing participants with an understanding of the steps for making bath bomb salt